O uso da Sitcom the fresh prince of bel-air como recurso audiovisual nas aulas de língua inglesa - SOARES, Vitoria Lorena da Cruz (Universidade Federal do Oeste do Pará, 2024)
Audiovisual resources play an important role in English teaching due to the possibility of being worked as didactic materials, they are responsible for promoting a greater contact between the reality of students and school. This qualitative research is based on authors that investigated the use of authentic materials in the classroom, the main goal was to analyze the contributions of the tv show “The Fresh Prince of Bel-Air” in English teaching with an activity made with five people between 20 and 24 years old. Data generation occurred through a questionnaire applied at the beginning of the research, a worksheet and a final questionnaire, in order to analyze the participants’ perceptions during the research. The meetings occurred remotely divided in two moments during the month of November 2021, and the data collected was analyzed using the interpretive method. Based on the results of this research, it was possible to observe that the tv series represent a teaching resource that encompasses both linguistic and cultural aspects, providing interactive activities to students. Although remote teaching presented its challenges during the research, it was noted that the series has a potential to dialog with the students' daily lives and also, open doors to stimulate English language teaching.